Animal model contributes to the development of intracranial aneurysm: A bibliometric analysis - Chen, Jia; Liu, Jing; Liu, Xin; Zeng, Chudai; Chen, Zhou; Li, Shifu; Zhang, Qian (Frontiers in Veterinary Science, 2022)
Abstract Introduction: Studies on intracranial aneurysm (IA) using animal models have evolved for decades. This study aims to analyze major contributors and trends in IA animal-related research using bibliometric analysis. Methods: Publications concerning IA animal-related publications were retrieved on the Web of Science. Microsoft Excel 2010, GraphPad Prism 6, VOSviewer, and CiteSpace were used to collect and analyze the characteristics of this field. Results: A total of 273 publications were retrieved. All publications were published between 1976 and 2021, and the publication peak year is 2019. Rats accounted for the most publications, followed by mice and rabbits. Japan (35.5%), the USA (30.0%), and China (20.1%) were the first three prolific countries. Although China ranks third in the number of publications, it still lacks high-quality papers and influential institutions. Stroke was the most prolific journal that accepted publications related to IA research using animal models. Circulation has the highest impact factor with IA animal-related publications. Hashimoto N contributed the largest number of papers. Meng hui published the first and second highest-cited publications. The keywords “subarachnoid hemorrhage,” “macrophage,” “rupture,” “mice,” “elastase,” “gene,” “protein,” “proliferation,” and “risk factors” might be a new trend for studying IA animal-related research. Conclusions: Japan and the USA contributed the most to IA animal-related studies, whatever researchers or institutions. Although China ranks third in terms of the number of publications, it should strengthen the quality of its publications. Researchers could keep an eye on the latest progress of Stroke, Journal of Neurosurgery, Neurosurgery, and Circulation for their high-quality IA animal-related articles. Using rats and mice IA models, especially mice, to investigate the molecular mechanisms of IA may be the frontier topic now and in the future.